A healthy dietary pattern associates with a lower risk of a first clinical diagnosis of central nervous system demyelination. (October 2019) - Black, Lucinda J; Rowley, Charlotte; Sherriff, Jill; Pereira, Gavin; Ponsonby, Anne-Louise; Lucas, Robyn M
Background: The evidence associating diet and risk of multiple sclerosis is inconclusive. Objective: We investigated associations between dietary patterns and risk of a first clinical diagnosis of central nervous system demyelination, a common precursor to multiple sclerosis. Methods: We used data from the 2003–2006 Ausimmune Study, a case–control study examining environmental risk factors for a first clinical diagnosis of central nervous system demyelination, with participants matched on age, sex and study region. Using data from a food frequency questionnaire, dietary patterns were identified using principal component analysis. Conditional logistic regression models ( n  = 698, 252 cases, 446 controls) were adjusted for history of infectious mononucleosis, serum 25-hydroxyvitamin D concentrations, smoking, race, education, body mass index and dietary misreporting. Results: We identified two major dietary patterns – healthy (high in poultry, fish, eggs, vegetables, legumes) and Western (high in meat, full-fat dairy; low in wholegrains, nuts, fresh fruit, low-fat dairy), explaining 9.3% and 7.5% of variability in diet, respectively. A one-standard deviation increase in the healthy pattern score was associated with a 25% reduced risk of a first clinical diagnosis of central nervous system demyelination (adjusted odds ratio 0.75; 95% confidence interval 0.60, 0.94; p  = 0.011). There was no statistically significant association between the Western dietary pattern and risk of a first clinical diagnosis of central nervous system demyelination. Conclusion: Following healthy eating guidelines may be beneficial for those at high risk of multiple sclerosis.